THE TRADITIONAL GENDER ROLES STEREOTYPES AS SEEN IN TROLLS (2016) THE DREAMWORKS ANIMATION MOVIE - Azza, Sekar Yolanda (Universitas Muhammadiyah Lampung, 2022)
In recent years, literature is not merely about poetry, prose, novel, short story but also the movie. One of the exciting animation movies is Trolls, produced by DreamWorks Animation in 2016. Undoubtedly, movies are not always about entertainment but can persuasively create an ideology in the kids' minds. Gender stereotypes are a negative impact of ideology that exists all over the world. Two research questions are formulated; what are the stereotypes towards women in Trolls movie and what ideology the movie seems to promote. This research aims to reveal the traditional stereotype towards women in Trolls movies and make the audience aware of the ideology of gender stereotypes towards women. This research applies library research with the descriptive qualitative method. Since this research analyzes gender stereotypes towards women in the movie, binary opposition theory can see the movie's structure. The writer concludes that women’s traditional gender roles stereotypes still exist in this movie. The stereotypes over women through Poppy as the character can be seen as irrational, weak, and submissive. The researcher also can find the patriarchal ideology. The movie promotes the gender issue in this film that shows the man is superior to the woman